Atrial tachycardia in a patient with arrhythmogenic right ventricular cardiomyopathy/dysplasia. Issue 4 (7th December 2012) - Mano, Hiroaki; Watanabe, Ichiro; Okumura, Yasuo; Sonoda, Kazumasa; Nagashima, Koichi; Nakai, Toshiko; Ohkubo, Kimie; Kofune, Tatsuya; Haruta, Hironori; Kofune, Masayoshi; Kunimoto, Satoshi; Hirayama, Atsushi
Abstract: We describe a 49‐year‐old woman with atrial tachycardia (AT) and arrhythmogenic right ventricular cardiomyopathy/dysplasia. Cardiac magnetic resonance images showed a markedly dilated right atrium and right ventricle. Electroanatomical mapping showed that the AT originated from the right atrial appendage.